ANALISIS HUBUNGAN KLIEN-AUDITOR : FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR (Studi Empiris pada Perusahaan Manufaktur di Indonesia Periode 2018-2020) - Nabila Aulia Azari; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
There are factors that can make a firm decide to do the auditor switching. The general reason is because they want to have their financial statement to be fairly valuated. This study included manufacture firms listed on Indonesia Stock Exchange 2018-2020 that have the variable need for the research. The aim is to exmine the factors that affect auditor switching. Those are change in management, subs, client size, client growth and auditor firm size.The datas used are secondary datas. Samples consist of 54 manfacture companies listed in Indonesia Stock Exchange within period of 2018-2020, choosen by purposive sampling method. The analysis used is logistic regression.The result of this study showed that change in management, subs, client size and size of auditor firm size doesn’t affect the auditor switch.. While the client growth is significantly affect the auditor switching. The logistic regression model is fit because the R square score is 0,311 or 31,1%.